COMPARISON OF THE MECHANICAL PERFORMANCE OF DENSE GRADING AND POROUS GRADING MIXTURE UTILIZED WITH CRUMB RUBBER MODIFIED BINDER - ESA, NOOR YUSRIAH; Aifa, Wan Nur; KASIM, NORHIDAYU; BASRI, NUR KHAIRIYAH (IIUM Engineering Journal, 2024)
Pavement and road networks play a very huge role in everyone’s daily lives to connect from one point to another point. With globalization, growth in the economy, and development, the number of vehicles traveling each day on the road increases rapidly over the years. Thus, the constant application of heavy loads together with Malaysia’s climatic factors lead the pavement to be susceptible to deterioration such as potholes and cracking. The service life and resistance of the pavement to deterioration can be improved with the incorporation of crumb rubber modified binder (CRMB) for asphaltic pavement. Hence, the objective of this research is to do a comparative evaluation of the mechanical performance of the CRMB that is utilized in dense grading and porous grading mixtures with varying percentage of crumb rubber replacement. The experimental portion of the research was done by substituting the crumb rubber at the replacement percentages of 12%, 14%, 16% and 18% (from the weight of asphalt binder) in preparing the modified binder that was further evaluated by conducting physical testing (penetration and softening point test). Then, the mechanical evaluation of dense and porous grading asphalt mixtures incorporating the crumb rubber was performed with Marshall stability and flow prior to comparing the strength performance for both asphalt mixtures. Based on the result obtained, it was found that the highest percentage of crumb rubber replacement, which is 18%, would give the highest level of stiffness and softening point on the binder. Furthermore, from the Marshall test, it was established that 16% of crumb rubber replacement on asphaltic binder is the most optimum for a porous mixture, given that the CRMB is 5% of the total mix. Nonetheless, at the same 16% of crumb rubber replacement, the value for Marshall test on the dense mixture shows an adverse result when compared to the control. Hence, it was concluded that the mechanical performance of CRMB utilized with porous mixtures shows more impressive results compared CRMB utilized with dense mixtures. ABSTRAK: Turapan dan rangkaian jalan raya memainkan peranan besar dalam kehidupan harian setiap orang dalam berhubung dari tempat ke tempat lain. Melalui globalisasi dan pertumbuhan ekonomi dan pembangunan, bilangan kenderaan bergerak setiap hari di atas jalan raya telah meningkat mendadak beberapa tahun kebelakangan ini. Oleh itu, beban berat berterusan bersama-sama faktor iklim Malaysia menyebabkan turapan jalan terdedah kepada kerosakan seperti jalan berlubang dan keretakan. Jangka hayat perkhidmatan dan rintangan turapan terhadap kerosakan jalan boleh diperbaiki melalui turapan asfaltik yang diubah suai dengan pengikat serbuk getah (CRMB). Justeru, kajian ini bertujuan bagi membanding prestasi mekanikal CRMB yang digunakan dalam campuran penggredan padat dan campuran berliang dengan peratusan penggantian serbuk getah berbeza. Kajian dijalankan dengan menggantikan serbuk getah pada peratusan penggantian pada 12%, 14%, 16% dan 18% (daripada berat pengikat asfalt) dalam menyediakan bahan pengikat yang diubah suai dan seterusnya dinilai melalui ujian fizikal (ujian takat penembusan dan takat lembut). Kemudian, penilaian mekanikal dijalankan ke atas campuran serbuk getah bersama asfalt bergred padat dan berliang. Kajian dijalankan mengguna pakai ujian kestabilan dan aliran Marshall sebelum membandingkan prestasi kekuatan bagi kedua-dua campuran asfalt. Keputusan menunjukkan dapatan peratusan pada 18% memberikan tahap kekakuan dan takat lembut tertinggi pada bahan penggantian pengikat serbuk getah. Tambahan, ujian Marshall menunjukkan 16% daripada penggantian serbuk getah pada pengikat asfaltik adalah paling optimum pada campuran berliang, di mana 5% daripada jumlah campuran merupakan CRMB. Namun, ujian Marshall pada campuran padat dengan penggantian serbuk getah 16% yang sama, menunjukkan dapatan nilai buruk berbanding pada kawalan. Oleh itu, prestasi mekanikal CRMB yang digunakan bersama campuran berliang menunjukkan dapatan lebih mengagumkan berbanding CRMB yang digunakan melalui campuran padat.